Design and Modeling of Modified Savonius Highway Wind Turbine - Venkatesh, P.M.; .Suresh, Dr.K; Babu, A.R. Vijay (International Journal of Engineering and Technology, 2018)
Abstractâ€” in this paper, the design and modeling of highway wind mill using savonius wind turbine has been done. The highway wind mill is nothing but the wind mill kept in the mid of the road so that , this wind mill utilize the fast moving wind which is produced from fast moving vehicles travels in the high way. In this work the required wind data have been collectedÂ  in highways and based on these values the design and fabrication have been made. The output of the wind turbine has been given to the power converter in order to get the constant power output.